Dynamic Analysis of A Deepwater Drilling Riser with A New Hang-off System - Li, Yan-wei; Liu, Xiu-quan; Wang, Jin-long; Chen, Guo-ming; Chang, Yuan-jiang; Sheng, Lei-xiang (China ocean engineering, 2024)
The safety of risers in hang-off states is a vital challenge in offshore oil and gas engineering. A new hang-off system installed on top of risers is proposed for improving the security of risers. This approach leads to a challenging problem: coupling the dynamics of risers with a new hang-off system combined with multiple structures and complex constraints. To accurately analyze the dynamic responses of the coupled system, a coupled dynamic model is established based on the Euler–Bernoulli beam-column theory and penalty function method. A comprehensive analysis method is proposed for coupled dynamic analysis by combining the finite element method and the Newmark β method. An analysis program is also developed in MATLAB for dynamic simulation. The simulation results show that the dynamic performances of the risers at the top part are significantly improved by the new hang-off system, especially the novel design, which includes the centralizer and articulation joint. The bending moment and lateral deformation of the risers at the top part decrease, while the hang-off joint experiences a great bending moment at the bottom of the lateral restraint area which requires particular attention in design and application. The platform navigation speed range under the safety limits of risers expands with the new hang-off system in use.